Effect of cyclosporin A and analogues on cytosolic calcium and vasoconstriction: possible lack of relationship to immunosuppressive activity. - Lo Russo, A. (1996)
1. The full therapeutic potential of the main immunosuppressive drug, cyclosporin A (CsA), is limited because of its side effects, namely nephrotoxicity and hypertension. Several lines of evidence suggest that the origin of both side effects could be CsA-induced vasoconstriction. However, the underlying molecular mechanisms are not well understood. 2. Diameter measurements of rat isolated mesenteric arteries showed an increase in noradrenaline- and [Arg]8vasopressin-induced vasoconstriction when arteries were pretreated with CsA. 3. Measurements in cultured vascular smooth muscle cells (VSMC) of either cytosolic calcium concentration or of 45Ca2+ efflux showed that CsA potentiated the calcium influx to several vasoconstrictor hormones: [Arg]8vasopressin, angiotensin II, endothelin-1 and 5-hydroxytryptamine. On the other hand, 45Ca2+ efflux in response to thapsigargin, which depletes calcium from intracellular pools, was not potentiated by CsA. 45Ca2+ uptake was not altered by CsA or by any of the analogues tested. 4. Time-course studies in cultured VSMC showed that maximal CsA-induced Ca2+ potentiation occurred after ca. 20 h and this effect was reversed over approximately the next 20 h. 5. To investigate the possible role played by the known intracellular targets of CsA, namely cyclophilin and calcineurin, CsA derivatives with variable potencies with respect to their immunosuppressive activity, were tested on the calcium influx to [Arg]8vasopressin. Derivatives devoid of immunosuppressive activity (cyclosporin H, PSC-833) potentiated calcium signalling, while the potent immunosuppressant, FK520, a close derivative of FK506, and MeVal4CsA, an antagonist of the immunosuppressive effect of CsA did not. The latter compound was unable to reverse the calcium potentiating effect of CsA. 6. Our results show that CsA increases the calcium influx to vasoconstrictor hormones in smooth muscle cells, which presumably increases vasoconstriction. Loading of the intracellular calcium pools appears not to be involved. Experiments with derivatives of CsA and FK520 suggest that interactions with cyclophilins and calcineurin are not the mechanism involved. This indicates, for the first time, that the immunosuppressive activity can be dissociated from the calcium potentiating effect of CsA in vascular smooth muscle.